Pengaruh Produk, Harga, Lokasi Terhadap Kepuasan Konsumen (Studi Kasus Perusahaan Beras Rantai Padi UD. Guna Karya Grogol) - Yuriska Wahyu Wijayanti; Ustadus Sholihin; Taufik Akbar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study to determine the effect of product, proce, and location on customer satisfaction either partially or simultaneously. The location of this research was conducted at UD. Guna Karya Grogol, Kediri Regency. The objects in this research are rice cutomers from UD. Guna Karya Grogol, Kediri Regency. This research is quantitative research. Data cllection was carried out using questionnaires, interviews, observation, documentation and literature, Data analysis was perfomed usuing validity test, realibility test, classic assumption test., multiple linear test, hypothesis test, determination test. From the result of the research that has been done, it shows that the first problem formulation regarding the product partially has a significance level effect on customers satisfaction. This is evidenced by the t count value of 2.850 with a significance level of 0,009. Price partially has a significance effect on consumer satisfaction. This is evidenced by the t count value of 1.948 with a significance level of 0,044. Place partially has a significant effect on customer satisfaction. Product,price and Place on customer satisfaction simultaneously have a significant effect on customer satisfaction. F count is 3.968 with a sig level of 0.021 where the figure is <0.05.